Comparison of pharmacological treatment alone vs. treatment combined with implantable cardioverter defibrillator therapy in patients older than 75 years - Cortés, Marcelino (ESC Heart Fail, 2018)
AIMS: Implantable cardioverter defibrillator (ICD) reduces mortality in selected patients. However, its role in patients older than 75 years is not well established. METHODS AND RESULTS: We performed a retrospective, non‐randomized study using a historical cohort from a single centre. Between January 2008 and July 2014, we assessed patients aged ≥75 years with left ventricular ejection fraction ≤ 35%, identifying 385 patients with a Class I or IIa recommendation for ICD implantation. At the decision of the patient or attending cardiologists, 92 patients received an ICD. To avoid potential confounding factors, we used propensity‐score matching. Finally, 126 patients were included (63 with ICD). The mean age was 79.1 ± 3.1 years (86.5% male). As compared with the medical therapy group, the ICD patients had a lower percentage of chronic obstructive pulmonary disease (19.0% vs. 38.1%, P < 0.05) and more frequent use of beta‐blockers (BBs) (85.7 vs. 70.0%, P < 0.05). Other treatments were otherwise similar in both groups. There were no differences related to age, aetiology, or other co‐morbidities. During follow‐up (39.2 ± 22.4 months), total mortality was 46.0% and cardiovascular events (death or hospitalization) occurred in 66.7% of the patients. A multivariate analysis revealed that only BB therapy was shown to be an independent protective variable with respect to mortality [hazard ratio 0.4 (0.2–0.7)]. ICD therapy did not reduce overall mortality or the rate of cardiovascular events. CONCLUSIONS: According to our results, the use of ICD, as compared with medical therapy, in patients older than 75 years did not demonstrate any benefit. Well‐designed randomized controlled studies in patients older than 75 years are needed to ascertain the value of ICD therapy.